Pengaruh Media Sosial, Brand Image, Dan Kualitas Produk Terhadap Keputusan Pembelian Pada Masa Pandemi Covid-19 (Study Kasus Om.Kopi) - Fairuz Dary Hanif; Achmad Agus Prioyono; Eris Dianawati (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This study was conducted to determine the effect of social media, brand image, and product quality on purchasing decisions in the midst of the COVID-19 pandemic. This study uses a quantitative approach with the method used in this study is multiple linear regression with the help of the sspss 20 program and using a sample of 200 respondents.The results of this study are the variables of social media, brand image, and product quality simultaneously have a positive and significant effect on purchasing decisions in the midst of the COVID-19 pandemic. Keywords: Social Media, Brand Image, Product Quality.